Iqbal Humanism and Human Rights - Mustofa Anshori Lidinillah; Mukhtasar Syamsuddin; Arqom Kuswanjono (Jurnal Filsafat "WISDOM", 2023)
Contrasting religion with human rights is a critical response that is unproductive because basically the relationship between religion and human rights is ambivalent. Meanwhile, freedom of religion is understood as part of human rights, but in reality, religious practices emerge which result in violations of human rights. This research wants to answer the question of how to bridge the relationship between religion and human rights by taking the case of Iqbal's concept of humanism, "How does Iqbal's humanism reconcile religion and human rights?" This study uses the hermeneutic-philosophical method by applying the following methodical steps: interpretation, analysis-synthesis, internal coherence, description, and heuristics. The results of the research show that Iqbal's humanism as a framing that reconciles religion and human rights based on a reciprocal relationship between religion and humanity. Tauhid as a working idea and the main spiritual basis for building a civilization with a human perspective contains values that are in accordance with the principles of human rights. The development of a new civilization with human insight must be pursued intellectually and vitally. Religion is a mode of human development as long as it is not accepted dogmatically. Therefore, Iqbal's humanism has a very strong relevance in efforts to uphold the principles of human rights in people's lives.